BRCA1 and BRCA2 as prognostic markers in oral squamous cell carcinoma: a minireview - Gedeonová, Dominika; Bianchi, Claretta; Štembírek, Jan; Hrdinka, Matouš; Chyra, Zuzana; Buchtová, Marcela; Hurník, Pavel; Blažek, Tomáš; Režnarová, Jana (Frontiers in Oncology, 2025)
Oral squamous cell carcinoma (OSCC), a subset of head and neck cancers, primarily originates in the epithelial tissues of the oral cavity. Despite advancements in treatment, the mortality rate for OSCC remains around 50%, underscoring the urgent need for improved prognostic markers. This review explores the role of the BRCA1 and BRCA2 genes—traditionally associated with breast and ovarian cancers—in the context of OSCC. We discuss the molecular pathways involving BRCA genes, their potential as diagnostics and prognostic biomarkers, and their implications for personalized treatment strategies, including addressing chemotherapy resistance. Furthermore, this review emphasizes the significance of genome stability in cancer progression and examines both current and emerging methodologies for detecting BRCA mutations in OSCC patients. Despite limited prevalence of BRCA mutations in OSCC compared to other cancers, their role in DNA repair and therapeutic response underscores their potential as clinical biomarkers. However, standardized, multicenter studies are still needed to validate their utility in OSCC management. A better understanding of the role of BRCA genes in OSCC could pave the way for more effective therapeutic approaches and improved patient outcomes.